J.J. Piernas López / L. Hancher / L. Rubini (Eds.). The Future of EU State aid Law and Policy: Consolidation and Expansion - Calvo Caravaca, Alfonso-Luis (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Este artículo reseña: J.J. Piernas López/L. Hancher/L. Rubini (Eds.). The Future of EU State aid Law and Policy: Consolidation and Expansion, EU Law Live Press, 2023. ISBN: 978-84-1369-561-7.